The Fh8 tag : a fusion partner for simple and cost-effective protein purification in Escherichia coli - Costa, Sofia Judite (2013)
Downstream processing is still a major bottleneck in recombinant protein production representing most of its costs. Hence, there is a continuing demand of novel and cost-effective purification processes aiming at the recovery of pure and active target protein. In this work, a novel purification methodology is presented, using the Fh8 solubility enhancer tag as fusion handle. The binding properties of Fh8 tag to a hydrophobic matrix were first studied via hydrophobic interaction chromatography (HIC). The Fh8 tag was then evaluated as a purification handle by its fusion to green fluorescent protein and superoxide dismutase. The purification efficiency of the Fh8-HIC strategy was compared to the immobilized metal ion affinity chromatography (IMAC) using the His6 tag. Results showed that the Fh8-HIC binding mechanism is calcium-dependent in a low salt medium, making the purification process highly selective. Both target proteins were biologically active, even when fused to Fh8, and were successfully purified by HIC, achieving efficiencies identical to those of IMAC. Thus, the Fh8 acts as an effective affinity tag that, together with its previously reported solubility enhancer capability, allows for the design of inexpensive and successful recombinant protein production processes in Escherichia coli.